Debt Versus Equity under Asymmetric Information - Narayanan, M. P. (Journal of Financial and Quantitative Analysis, 1988)
In a world of asymmetric information in which only the insiders know the quality of the firm, it is claimed that debt, even if it is risky, is more advantageous than outside equity because issuance of debt is less attractive to inferior firms. The advantage to debt arises from the fact that it can keep unprofitable firms out of the market, thus improving the average quality of firms in the market. This advantage exists even if the firms cannot be perfectly sorted in the signaling equilibrium.